SENAM AEROBIC EXERCISER CHI MACHINE LEBIH EFEKTIF DARIPADA BERSEPEDA STATIS MENURUNKAN KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS TIPE II DI PUSKESMAS MENGWI III - I Wayan Surasta; Ketut Tirtayasa; I Putu Gede Adiatmika (Sport and Fitness Journal, 2013)
Diabetes mellitus is a metabolic syndrome with hyperglycemic in characteristic. Exercise is one of intervention hopefully curing diabetes mellitus. The objective of the study was to analyze effect of aerobic exerciser chi- machine  and static bicycle   reducing of blood glucose level type 2 diabetes mellitus. Design   of study quasi eksperiment, pre test and post test control group design. Group 1 (10 samples) was provided   aerobic exercise chi-machine and group 2 (10 samples) static bicycle   15 minutes three time a week the duration of six weeks. Study  locati was at Mengwi III  Public Health Center, of Badung Regency with 20 samples was selected by using simple random sampling from the patient of diabetes mellitus type 2. Result of study is showed  aerobic exerciser chi-machine reduced the mean of blood glucose level of 124 mg%. Static bicycle  reduced mean of blood glucose level of 70.4 mg%. Conclusion of study aerobic exercise chi-machine more effective 17% than static bicycle exercise (p: 0,028) for reducing of blood glucose level type 2 diabetes mellitus.